GAYA KEPEMIMPINAN SITUASIONAL TERHADAP MOTIVASI KERJA KARYAWAN PADA PT GARUDA INDONESIA (PERSERO) TBK CABANG KUPANG - Sanjung Koniswara; Tri Suris Lestari (EKOBIS, 2019)
Based on Kompas news, it is known that several pilots who are members of the Garuda Pilot Association (APG) conducted a strike because of management problems. Employees (pilots) assume that management always makes unilateral decisions on every policy made. This study aims to determine the effect of situational leadership style on employee work motivation at PT Garuda Indonesia (Persero) Tbk Kupang Branch. The independent variable under study is the situational leadership style (X), while employee work motivation (Y) as the dependent variable is examined. Situational leadership style variables are measured using indicators of instruction, consultation, participation, and delegation. The variable work motivation of employees is measured by using indicators of willingness to assume responsibility, achievement motivation, and engagement. This study uses a sample of 25 respondents, namely the executive employee of PT Garuda Indonesia (Persero) Tbk Kupang Branch. While sampling uses a saturated sampling technique. The data used are primary data and secondary data collected through questionnaires and observations. The results of this study based on the results of the correlation analysis/relationship between situational leadership style and employee work motivation obtained a correlation value of 0.677 which is classified as positive and strong. The results of simple linear regression analysis obtained the equation Y = 31.931 + 0.599X, X regression coefficient of 0.599 states that every 1% increase in the value of situational leadership style, the motivation value increases by 0.599. The t-test shows that situational leadership style (variable X) partially proved to have a positive effect on employee work motivation (variable Y). The magnitude of the influence of situational leadership on employee motivation is 45.9%, while 54.1% is influenced by other factors such as the desire to live, the desire for a position, the desire for power and the desire for recognition, which is not examined by the researcher. Based on the results of the data analysis, it is suggested that in increasing employee work motivation, it is necessary to have guidance and training in the field of tasks as well as increased motivation related to the needs of employees both internally and externally. For other researchers, it is expected that they can expand the object of their research and not only limited to the PT Garuda Indonesia (Persero) Tbk Kupang Branch but can be done in other institutions related to the objectivity of employee motivation. Keyword : situational leadership, motivation, employees